Toxicity of a dental adhesive compared with ionizing radiation and zoledronic acid - Alcaraz, Miguel (Med Oral Patol Oral Cir Bucal, 2015)
BACKGROUND: To determine the toxicity of aqueous dilutions of a universal self-priming dental adhesive (DA) and comparing these with those elicited by exposure to ionizing radiation (IR), Zoledronic acid (Z) treatment and the synergic effects of the combined treatment with IR+Z. MATERIAL AND METHODS: The genotoxic effect of DA was determined by the increase in the frequency of micronuclei in cytokinesis-blocked in cultured human lymphocytes before and after exposure to 2Gy of X-rays. The cytotoxic effect was studied by using the MTT cell viability test in normal prostate cell lines (PNT2) after exposure to different X-ray doses (0Gy-20Gy). The cell lines divided into different groups and treated with different test substances: DA in presence of O2, DA in absence of O2, Z-treated and control. RESULTS: An in vitro dose-dependent and time-dependent cytotoxic effect of DA, Z and IR on PNT2 cells (p>0.001) was demonstrated. DA without-O2, following the recommendations of manufacturers, had a more pronounced effect of increasing cell death than DA with-O2 (p<0.001). In the genotoxicity assay, DA at 25% of its original concentration significantly increased chromosome damage (p<0.001). The samples studied were found to be toxic, and the samples photo-polymerized in absence of O2 showed a bigger cytotoxic effect comparable to the additive toxic effect showed by the combined treatment of IR+Z. CONCLUSIONS: Additional effort should be carried out to develop adhesives, which would reduce the release of hazardous substances; since toxic effects are similar to that reported by other agents whose clinical use is controlled by the health authorities. Key words: Micronucleus, toxicity, dental adhesive, zolendronic acid, radiation effects.